Kepemimpinan Pendidikan Di Sekolah Dasar - Idawati Idawati; Rosliah Rosliah; St. Nurwafiqah Maghfirah; Tria Mulya Utari; Hikmah Idris; Gusnita Gusnita (Mathematics Education Study Program, 2025)
A leader by definition is someone who has the ability to influence the behavior of others in their work by using authority. Leadership plays a crucial role in achieving the goals of an institution or organization. Responsible and trustworthy leadership can drive an institution or organization forward and foster its development. Many factors can influence an individual's performance. As an educational leader, one must be able to exert influences that motivate teachers or subordinates to carry out their duties effectively, thereby improving their performance. This study employs a qualitative descriptive approach. The method used involves reviewing journals related to educational leadership in elementary schools. Data collection comes from various sources, such as journals, books, and interviews, serving as references to gain an in-depth understanding of educational leadership in elementary schools. The leadership of the school principal is a key determinant of the successful realization of the functions and goals of national education. It is not solely the greatness of teachers that ensures success, but rather the principal who facilitates, enables, and drives teachers' performance, allowing them to fulfill their roles and unlock their potential for goodness and responsibility. There are four common leadership behavior patterns often referred to as leadership styles: instructive, consultative, participative, and delegative. The competencies that a school principal must demonstrate as a leader can be analyzed based on their personality, knowledge of educational staff, vision and mission of the school, decision-making ability, and communication skills.